Mercury Contamination on Aquatic Organisms in related to Artisanal Small-scale Gold Mining Activity in Indonesia: A Mini Review. Issue 1 (1st July 2022) - Yoga, G P; Sari, A A; Nurhati, I S; Yustiawati,; Andreas,; Hindarti, D
Abstract: Artisanal Small Scale Gold Mining (ASGM) is the largest source of Hg pollution in the environment. Indonesia has ratified the Minamata convention in 2013. Mercury pollution to the aquatic environment is a great concern due to its potential impact may threat the aquatic ecosystem. In this study we conduct a mini literature review dealing with the impact of mercury pollution on aquatic organisms in Indonesia, this study provides an overview of mercury contamination in fish and macroinvertebrates in Indonesia which is related to ASGM activities, based on peer-reviewed literature recorded in the Scopus database (www.scopus.com). Keywords mercury OR Hg AND ASGM AND Indonesia was used to retrieve literatures from the database. The identified articles were screened for relevance at the title, abstract, and full text level using predefined inclusion criteria. The mercury accumulation in freshwater fish and macroinvertebrates were ranged from 0.005 mg/kg to 19 mg/kg, and from 0.002 mg/kg to 1, 46 mg/kg, respectively. While mercury accumulation in in marine fish and macroinvertebrates were from 0, 014 mg/kg to 57 mg/kg and 0.002 mg/kg to 2.99 mg/kg, respectively. The highest mercury accumulation in freshwater fish was found in Manado, North Sulawesi and the lowest was in Talawaan Watershed, North Sulawesi, while in Marine fish, the highest Hg accumulation was also found in Manado, North Sulawesi, and the lowest accumulation was found in Buyat, North Sulawesi. Introduction